Diversified Urbanization : The Case of Côte d'Ivoire - Fall, Madio; Coulibaly, Souleymane (Washington, DC: World Bank, 2016)
Côte d’Ivoire seeks a development strategy to reach middle-income status—a challenge that would require annual growth rates averaging 10 percent over the next 13 years. Global experience of both developed and emerging economies shows that GDP per capita rises with increased urbanization. However, Côte d’Ivoire’s economy is underperforming relative to its level of urbanization. The country’s urbanization has been negatively correlated with income per capita since the late 1970s, and poverty has been increasing.